The role of government debt in economic growth - Afonso, António (2014)
We study the effect of public debt on economic growth for annual and 5-year average growth rates, as well as the existence of non-linearity effects of debt on growth for 14 European countries from 1970 until 2012. We also consider debt-to-GDP ratio interactions with monetary, public finance, institutional and macroeconomic variables. Our results show a negative impact of -0.01% for each 1% increment of public debt, although debt service has a 10 times worse effect on growth. In addition, we find average debt ratio thresholds of around 75%. Belonging to the Eurozone has a detrimental effect of at least -0.5% for real per capita GDP, and the banking crisis is the most harmful crisis for growth.